Issues of Natural Gas Infrastructure Development in South-Eastern Europe - Osmanovna, Khalova Gul’nar; Andreevna, Isayeva Elena; Igorevich, Illeritskiy Nikita; Alekseevna, Smirnova Vera (International Journal of Energy Economics and Policy, 2019)
The adoption of the Third Energy Package has become a new stage in the evolutionary process of the EU gas market, its liberalization and modernization. Natural gas occupies a significant place in the energy balance of most EU countries; therefore, all EU countries are interested in an efficient and uninterruptedly functioning gas transmission system. In addition to the pan-European gas corridor routes developed by the European Commission, there are a number of significant regional-level gas transportation projects that complement large gas corridors. The article considers the countries of Southeastern Europe of the Balkan Peninsula, which in the future can become one of the main corridors for the supply of natural gas to Europe. However, it depends on the results of cooperation between Russia, Turkey and European Union. Keywords: Energy Supply, Natural Gas Supply, Energy Cooperation JEL Classifications: Q3, Q4 DOI: https://doi.org/10.32479/ijeep.8548